Advanced HF Communications for Remote Sensors in Antarctica - Pijoan, Joan Lluis (2019)
The Antarctica is a continent mainly devoted to science with a big amount of sensors located in remote places for biological and geophysical purposes. The data from these sensors need to be sent either to the Antarctic stations or directly to the home country. For the last 15 years, La Salle has been working in the application of HF communications (3‚Äì30¬†MHz) with ionospheric reflection for data collection of remote sensors in Antarctica. We have developed and tested the several types of modulations, the frame structure, the radio-modem, and the antennas for two different scenarios. First, a long-range transequatorial (approximately 12,800¬†km) and low-power communication system is used as an alternative to satellites, which are often not visible from the poles. This distance is covered with a minimum of four hops with oblique incidence in the ionosphere. Second, a low-power system using near vertical incidence skywave (NVIS) communications provides coverage in a surface of approximately 200‚Äì250¬†km radius, a coverage much longer than any other systems operating in either the VHF or UHF band without the need of line of sight.